2004
DOI: 10.1260/1351010042250385
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Contribution of Acoustic Resonators Found in Serbian Orthodox Churches

Abstract: A study of a number of Serbian Orthodox medieval churches, during their reconstruction or archeological investigation, revealed the presence of acoustical resonators. This paper offers a review of the resonators discovered to date. In addition, laboratory experiments were conducted on several resonators removed from churches in order to clarify their function. Based on the relevant literature, laboratory experiments, and analyses of acoustical characteristics of the worship spaces where resonators were found, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
(12 reference statements)
0
17
0
Order By: Relevance
“…The first acoustic research into the medieval ceramic vessels of Serbia, based on the calculations of acoustic parameters on available drawings of the vessels, were published in 1984 for two acoustic vessels found in the church of the village of Komarane from the 14 th century (Kalić 1984). Laboratory measurements on the same vessels (Mijić & Šumarac Pavlović 2004) showed significantly lower resonant frequencies (124 Hz and 131 Hz) compared to Kalić's calculations (166 Hz). The divergence is on account of the thickness of the final layer of mortar, which was not part of Kalić calculations but was added to the opening of the resonator in the laboratory measurements in order to simulate the original state of the inbuilt resonator.…”
Section: Acoustic Studiesmentioning
confidence: 52%
See 4 more Smart Citations
“…The first acoustic research into the medieval ceramic vessels of Serbia, based on the calculations of acoustic parameters on available drawings of the vessels, were published in 1984 for two acoustic vessels found in the church of the village of Komarane from the 14 th century (Kalić 1984). Laboratory measurements on the same vessels (Mijić & Šumarac Pavlović 2004) showed significantly lower resonant frequencies (124 Hz and 131 Hz) compared to Kalić's calculations (166 Hz). The divergence is on account of the thickness of the final layer of mortar, which was not part of Kalić calculations but was added to the opening of the resonator in the laboratory measurements in order to simulate the original state of the inbuilt resonator.…”
Section: Acoustic Studiesmentioning
confidence: 52%
“…Therefore, today is only possible to conduct acoustic measurements on those vessels in the laboratory or build corresponding three-dimensional models of the vessels and the entire space and thus examine acoustics through virtual acoustic simulation. The only acoustic study on acoustic vessels from medieval Serbia, based on the laboratory measurements of a single artifact, showed that the vessel was tuned to low frequencies (Mijić & Šumarac-Pavlović 2004), on which the absorption of usually wooden furniture (iconostasis, icon stands, pulpit, etc.) is less effective (Valière et al 2013: 78).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations